2018
DOI: 10.1029/2018gl078509
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of STEVE: Particle Precipitation or Ionospheric Skyglow?

Abstract: One of the recent developments in ionospheric research was the introduction of a subauroral spectacle called STEVE (Strong Thermal Emission Velocity Enhancement). Although STEVE has been documented by amateur night sky watchers for decades, it is an exciting new upper atmospheric phenomenon for the scientific community. Observed first by amateur auroral photographers, STEVE appeared as a narrow luminous structure across the night sky. Currently, only one scientific study has focused on STEVE, revealing that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 26 publications
10
66
0
Order By: Relevance
“…The STEVE arcs are also located equatorward of the bulk of the electron plasma sheet precipitation. In the second and third events, STEVE is not associated with >~1 keV precipitation, in agreement with Gallardo‐Lacourt, Liang, et al ().…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The STEVE arcs are also located equatorward of the bulk of the electron plasma sheet precipitation. In the second and third events, STEVE is not associated with >~1 keV precipitation, in agreement with Gallardo‐Lacourt, Liang, et al ().…”
Section: Resultssupporting
confidence: 88%
“…The subauroral precipitation structure and upward FAC are strikingly different from typical SAID events (Anderson et al, , ). Moreover, this electron precipitation was not seen for the STEVE event studied by Gallardo‐Lacourt, Liang, et al (), which did not have a picket fence, and could not be examined for the MacDonald et al () event due to the lack of particle measurements. The ~2 mW/m 2 (erg/cm 2 /s)‐integrated energy flux and ~2‐keV mean energy of this population can drive visible emission dominated by the 557.7‐nm wavelength peaking at 120‐km altitude ( I 557.7 ~ 2.5 kR and I 630.0 ~ 1.5 kR based on the Global Airglow code modeling (Solomon et al, ), not shown), which could explain the green emission of the picket fence that appears at lower altitude of the mauve arc.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, the enhancement is part of the spectrum unique to STEVE and not the ambient night airglow that is seen immediately north and south of, and within, STEVE. This is consistent with previous studies which have utilized red‐line imagers to identify and track this type of structure (Gallardo‐Lacourt, Nishimura, et al, , Gallardo‐Lacourt, Liang, et al, ; MacDonald et al, ). When analyzing the remaining spectrum not associated with these three prominent emission lines, we can see a noticeable luminosity enhancement within STEVE.…”
Section: Discussionsupporting
confidence: 91%
“…All examples that have been observed in scientific data (e.g., all‐sky images) have been well equatorward of the proton aurora and either at the equatorward edge of diffuse aurora or equatorward of the (traditional) aurora (Gallardo‐Lacourt, Nishimura, et al, ). Finally, there have been transits through Steve by DMSP, POES, and Swarm spacecraft, and in no instance has there been any evidence of electron or proton precipitation that could be the cause of Steve's luminosity (Gallardo‐Lacourt, Liang, et al, ; MacDonald et al, ; Nishimura et al, ), suggesting that Steve is likely not aurora. All of this evidence led a scientist to suggest that “Steve” could be made into a backronym, STEVE, representing “Strong Thermal Emission Velocity Enhancement.” Beginning with the first published scientific article (MacDonald et al, ), this has become the accepted scientific name of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Skyglow in the form of a narrow in magnetic latitude, east‐west‐aligned mauve “ribbon” and occasionally green rayed “Picket Fence” equatorward of the auroral zone was often reported by amateur photographers. MacDonald et al () have named the mauve arcs as Strong Thermal Emission Velocity Enhancement (STEVE) because of the relation to strong plasma streams – subauroral ion drifts (SAID), with highly elevated electron temperature, Te5000 K. Their features have been detailed by Gallardo‐Lacourt, Liang, et al (), Gallardo‐Lacourt, Nishimura, et al (), Nishimura et al (), and Archer, Gallardo‐Lacourt, et al (). In particular, Gallardo‐Lacourt, Nishimura, et al () statistical study shows that STEVE occurred during the recovery phase of substorms.…”
Section: Introductionmentioning
confidence: 99%